Research on Characteristics of Unloading Zone at Lower Dam Site of Banda Hydropower Station - HE Shutao; DENG Hui; WU Xiaojun; XIAO Yuyue; SU Hang (Renmin Zhujiang)
In order to study the characteristics of unloading zone at the lower dam site of Bandahydropower station, this paper firstly introduces the mechanism of unloading and the researchbackground of unloading zone division, then according to the project profile and slope unloadingcondition in dam area, divides the unloading zone quantitatively by the fracture opening, wavevelocity ratio and adit seismic wave velocity index, and finally obtains the comprehensive divisionresults and unloading zone characteristics. The results show that the development depth ofunloading zone is positively related to the elevation, the ductile shear zone will increase theunloading depth, the unloading degree on the left bank is generally greater than that on the rightbank, and the unloading degree on the ridge is greater than that on the gully.